The fragmented nature of physical education and sport in European schools is a cause in the decline in interest of youth sport - Goggaki, K. (ΧΙΙΙ Olympic Congress, International Olympic Committee, 2009)
(2009). Goggaki, Konstantina. Assistant Professor in Philosophy of Sport, University of Athens, Greece. The fragmented nature of physical education and sport in European schools is a cause in the decline in interest of youth sport. XIII OLYMPIC CONGRESS, Contributions, International Olympic Committee, Copenhagen, pp. 634-635.  Sport is not an integral part of mainstream education in most European schools and as a result is inadequate as an education tool. Gymnastics for example, is an activity that is practically devoid of pedagogical content and is reduced to being a secondary activity that is not connected to the overall educational process. The modern school system does not have real substance and absorbs the students’ leisure time through the implementation of a static curriculum.  How can this situation be changed? In what way can the Olympic family intervene in a case which seems to be the sole responsibility of governments? And how can this intervention be effective? There is much more that needs to be done in this area.